Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Nasabah Melakukan Cicilan Emas Di Bank Syariah Indonesia KCP Pandeglang - Ahmad Tabrani; Wazin Baihaqi; Nana Suryapermana (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
This study aims to find out what strategic factors can increase the customer's decision to make gold installments during factual conditions, produce a relationship of influence and dependence between variables that affect the customer's decision to make gold installments on factual conditions, find what strategic factors can increase the customer's decision to make gold installments during potential conditions, and find the potential indirect influence of dependence for each factual condition variables that influence the decision of customers to make gold installments, This research method uses a structural research paradigm using MICMAC tools, informants / actors in this study are pawning appraisal, funding and transaction staff, customer service and 4 gold installment customers. The results showed that the MICMAC analysis of the typology of strategic variables based on the strength of influence found 4 classifications of quadrants of variables, this classification has been tested using MDI and MII. The potential consistency test for this classification has also been tested and the results are stable obtained quadrant I dominant variables with dimensions of selection of the place of distribution: 1, quadrant II of relay variables with 17 dimensions including problem recognition: 2, introduction of information: 2, evaluation of alternatives: 2, purchase decisions: 2, after-purchase behavior: 2, product selection: 2, brand selection: 1, selection of channeling places: 1, and the amount of purchase: 1, and payment method: 2, quadrant III of the output variable there is no one dimension that enters quadrant III, and quadrant IV of the autonomous variable with 2 dimensions of which are brand selection: 1, and the time of purchase: 1